2015
DOI: 10.1016/j.atmosenv.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

On the evaluation of global sea-salt aerosol models at coastal/orographic sites

Abstract: Sea-salt aerosol global models are typically evaluated against concentration observations at coastal stations that are unaffected by local surf conditions and thus considered representative of open ocean conditions. Despite recent improvements in sea-salt source functions, studies still show significant model errors in specific regions. Using a multiscale model, we investigated the effect of high model resolution (0.1 degrees x 0.1 degrees vs. 1 degrees x 1.4 degrees) upon sea-salt patterns in four stations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…2; Sievering et al, 2004;Allen et al, 1997). For comparison, coarse SSA dominates the aerosol mass at Baring Head, with concentrations of 6-10 µg m −3 (Jaeglé et al, 2011;Spada et al, 2015). Similar seasonal cycles of DMS and nssSO 4 were recorded at Cape Grim (Ayers, 1991), and the observed diurnal inverse correlation between sulfur dioxide and DMS at Baring Head was applied to estimate yield and the potential contribution to aerosols (de Bruyn et al, 2002).…”
Section: Regional Contextmentioning
confidence: 95%
“…2; Sievering et al, 2004;Allen et al, 1997). For comparison, coarse SSA dominates the aerosol mass at Baring Head, with concentrations of 6-10 µg m −3 (Jaeglé et al, 2011;Spada et al, 2015). Similar seasonal cycles of DMS and nssSO 4 were recorded at Cape Grim (Ayers, 1991), and the observed diurnal inverse correlation between sulfur dioxide and DMS at Baring Head was applied to estimate yield and the potential contribution to aerosols (de Bruyn et al, 2002).…”
Section: Regional Contextmentioning
confidence: 95%
“…also provided a detailed evaluation of the gas-phase chemistry for the year 2010 over Europe in the context of AQMEII-Phase2. The initial model developments focused on the implementation of the mineral dust aerosol component (NMMB/BSC-Dust; Pérez et al, 2011;Haustein et al, 2012) and the sea-salt aerosol component (Spada et al, 2013(Spada et al, , 2015. The implementation and evaluation of other relevant aerosols will soon be described elsewhere (Spada et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The initial model developments focused on the implementation of the mineral dust aerosol component (NMMB/BSC-Dust; Pérez et al, 2011;Haustein et al, 2012) and the sea-salt aerosol component (Spada et al, 2013(Spada et al, , 2015. The implementation and evaluation of other relevant aerosols will soon be described elsewhere (Spada et al, 2017). This initiative aims at developing a fully coupled chemical multiscale (global/regional) weather prediction system that resolves gas-aerosol-meteorology interactions and provides initial and boundary conditions for embedded high-resolution nests in a unified dynamics-physicschemistry environment.…”
Section: Introductionmentioning
confidence: 99%
“…As AD accompanied by typhoon outflow circulation, it could bring huge amounts of SSs from the surface of the Bashi Channel to Kaoping River Valley (Park et al, 2004;Tsai et al, 2010). Previous studies (Quinn et al, 2003;Xu et al, 2013;Spada et al, 2015) indicated that the estimated SSs are based on the assumption that Na + and Cl − are mainly derived from seawater and hence excluding the contribution from non-sea-salt ionic species (nss-WSIs) such as K + , Mg 2+ , Ca 2+ , SO 4 2− , and HCO 3 − , thereby allowing Cl loss from SSs through chemical reactions with acidic constituents of ambient particulate matter. However, Cl − is often partially depleted because of its reactions with acidic compounds such as sulphuric and nitric acids (Tsai et al, 2010).…”
Section: Resultsmentioning
confidence: 99%